The Use of Basketball Variations in Ukrainian General Secondary Education Institutions for Enhancing High School Students' Physical Capacity - Anheliuk, Iryna; Naumchuk , Volodymyr (JUMORA: Jurnal Moderasi Olahraga, 2023)
Amidst the ongoing reforms in Ukraine's educational sector, prioritizing students' health and improving their physical prowess has become imperative. This study explores the feasibility and effectiveness of integrating diverse forms of traditional basketball into high school physical education lessons to enhance the work capacity of students. The research cohort comprised 29 male 11th-grade students. The assessment of physical work capacity focused on the Harvard Step Test (HST), utilizing its metrics to measure students' development. Univariate analysis was employed for data analysis. Results indicated a satisfactory level of physical fitness among students, slightly below the established norm. These findings emphasize the need to incorporate various basketball derivatives, including streetball, korfball, netball, rezball, ringball, slamball, and cestoball, into the general secondary education physical education curriculum. The comprehensive adoption of these variations not only improves high school students' functional capabilities and enhances their enthusiasm for physical activities but also deepens their understanding of the objectives of physical culture, contributing to the broader objectives of the educational sphere. Future research should focus on defining a set of informative indicators and developing comprehensive means of enhancing motor skills and proficiency in basketball. This approach is expected to boost high school students' work capacity and foster increased interest in basketball and its derivatives. Keywords: physical capacity, basketball variations, high school students, physical education lesson.